COMPARISON OF DIRECT AND INDIRECT LDL CHOLESTEROL LEVELS CALCULATIONS (FRIEDEWALD & CHEN) IN PATIENTS AT RSUP PROF. DR. I.G.N.G. NGOERAH DENPASAR - Setyawati, Putu Ayu; Herawati, Sianny; Subawa, A.A Ngurah (E-Jurnal Medika Udayana; Vol 13 No 11 (2024): E-Jurnal Medika UdayanaDO - 10.24843/MU.2024.V13.i11.P11, 2024)
High LDL cholesterol levels are the risk factor for coronary heart disease. Proper measurement of LDL levels helps in determining the accuracy of evaluation and therapy. Measurement of LDL cholesterol levels can be done by direct or indirect methods. Until now, the Friedewald formula is a method that is still often used but has shortcomings. So many new calculation formulas have emerged, one of which is the Chen Formula. This study was to comparison of LDL-direct with the LDL levels measured by the Friedewald and Chen formula. This study was conducted at Prof. Dr. I.G.N.G. Ngoerah Hospital, Denpasar. Samples used were 95 patients who performed lipid profile examinations in the period April-June 2023 with consecutive sampling techniques. Based on the independent t-test of LDL recruited with Friedewald and Chen indirect, the p-value was 0.205 and 0.206 respectively (p> 0.05), thus it was did not find any significant differences between LDL cholesterol direct and indirect (Friedewald & Chen).